BS EN 61156-8. Multicore and symmetrical pair/quad cables for digital communications. Part 8. Symmetrical pair/quad cables with transmission characteristics up to 1 200 MHz. Work area wiring. Sectional specification (28th September 2021) - British Standards Institution,
No abstract available